Levels of Biochar and NPS Fertilizer Rates on Growth, Yield Component, and Yield of Maize (Zea mays L.) at Guto Gida, Western Ethiopia - Abdela Tufa; Adugna Hunduma; Mohammad Najmus Saquib Hasan; Fayera Asefa; B. C. Nandeshwar (Advances in Agriculture)
Mixed application of organic and inorganic fertilizers in mixture improves soil fertility and crop productivity. However, the identification of combined application level is important. Therefore, a field experiment was conducted in 2020 in the Guto Gida district to assess the effect of maize cob biochar levels and inorganic NPS fertilizer rates on the growth and yield of maize. The study was conducted in factorial combinations of five rates of maize cob biochar and three rates of inorganic NPS fertilizer using a randomized complete block design with three replications. The main effect of the biochar level and NPS rate significantly affected crop phenology and biomass yield, whereas the number of kernels ear−1 was affected by the main effect of NPS rate. The combined application of biochar and NPS fertilizer significantly influenced plant height, leaf area index, ear weight, thousand kernel weight, grain yield, and percentage of grain yield. The interaction of biochar at 8 t·ha−1 with 100 kg·ha−1 NPS resulted in highest leaf area index (5.56), grain yield (7.03 t·ha−1), and yield increment (18.11%) followed by 8 t·ha−1  × 50 kg·ha−1 and all biochar levels with 100 kg·ha−1 NPS. In addition, the highest values of ear weight (276 g) and thousand kernel weight (47.81 g) were recorded in plots treated with combined application of biochar and NPS fertilizer at rates of 8 t·ha−1 × 50 kg·ha−1 and 4 t·ha−1 × 100 kg·ha−1, respectively, whereas plots not treated with both biochar and NPS resulted in lowest yield followed by 0 t·ha−1 × 50 kg·ha−1. In conclusion, integrated application of maize cob biochar at 8 t·ha−1 with NPS fertilizer at 50 kg·ha−1 improved the yield of maize by about 16.85% with net benefit of 61700.50 ETB ha−1 and marginal rate of return 733.68%, and therefore, the application of biochar at this rate with mineral NPS fertilizer at 50 kg·ha−1 is considered as suitable for the study area.